The Flouting of Conversational Implicature in the Headlines and Taglines - Aninda Dampit Laila Kartika (Universitas Gadjah Mada, 2012)
This research attempts to describe the kinds of flouting of Grice‟s Cooperative Principle maxims and explain the type of maxim mostly and least flouted in the headlines and taglines which are found in two magazines, Travel+Leisure and Wine Enthusiast. It is also aimed to see whether the headlines and taglines are able to describe the products or services. This study is presented within the framework of pragmatics. The result shows from 60 data found, 14 of the headlines and taglines in the Travel+Leisureand 16 in Wine Enthusiast magazine are mostly identified flouting the combination of maxims; maxim of Quantity and Quality. In addition, the maxim of Quality and the maxim of Manner are least flouted by the headlines and taglines in both magazines. The result also shows that the headlines and taglines are unable to fully describe the products or services unless the body copy is also provided.